Education and Knowledge Production in Workers’ Struggles: Learning to resist, learning from resistance - Bleakney, David; Choudry, Aziz (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
Trade unions and other sites of community-labour organizing such as workers centres are rich, yet contested spaces of education and knowledge production in which both non-formal and informal / incidental forms of learning occur. Putting forward a critique of dominant strands of worker education, the authors ask what spaces exist for social movement knowledge production in these milieus? This article critically discusses the prospects, tensions and challenges for effective worker education practice in trade unions, alongside a discussion of informal learning and knowledge production in migrant and immigrant worker organizing. We consider how worker education practices within trade unions might best be built to support critical thinking, the collective power of working people and cultures of resistance, and the significance of knowledge and learning in community-labour struggles.